Developing language training as an effective channel of cross-cultural education: a contemporary methodological approach in Chinese training for international students - Shanshan, Song (University Pedagogical Journal, 2022)
By recounting the connection between language and culture, this paper examines the relationship between language learning and cross-cultural competence development, and highlights the critical role of culture input in language teaching. Then the article introduces the national policy requirements for the cultivation of cross-cultural competence of international students in the universities in China. This requirement directly affects the curriculum objectives of Chinese courses for international students in China’s modern universities. It requires that Chinese language education should not be limited to the cultivation of language skills, but also need to introduce relevant cultural elements, to cultivate the students’ cross-cultural competence. Then the article expounds on how Chinese teachers combine different Chinese cultural elements into different language courses to implement cross-cultural education.